Perancangan Pembangkit Listrik Tenaga Surya Off Grid Untuk Penerangan dan Pengeras Suara pada Mushola Hidayatullah Desa Harapan Baru - Yudi Chandra (entries, 2022)
Solar energy is an energy that form the light and heat from the sun. This energy can be utilized by using technologies such as solar heating, solar photovoltaics, solar thermal electricity, solar building energy, and artificial photosynthesis. Solar energy provides many benefits for human life. One of the utilization of solar energy can be implemented is in the form of Solar Power Plants (PLTS). The Final Project a solar power plant designed which is located in Harapan Baru Village, kecamatan Matan Hilir Selatan, Ketapang Regency. The solar power plant component using an off grid system. The off grid PLTS system is used to a substitute for electricity, when source of PLN goes out. The design of solar power plant by selecting the solar components, calculating the power components will be needed, calculating the solar power components, then determining the location of the solar panel used. after the PLTS components have known the types and specifications, then calculation cost of budged plan recommended in the design of PLTS with this off grid system. The components used in solar power plants with this off grid system are solar panel, batterie, inverter, and solar charge controllers. This solar power generation system designed to supply electricity needs of the mosque when the PLN power source is off. Where this system uses consist of component are 5 piecs solar panels 100 Wp, an inverter capacity of 800 Watt, batteries with capacity of 60 Ah 12 Volt and a solar charge controller with capacity of 60 A cost of budget recommendeed is cost of Rp. 10,127,000.00.